The Practice of 'Aisyiyah Women's Community in Communicating during the Covid 19 Pandemic - Dede Lilis Chaerowati; Tia Muthiah Umar; Mohamad Subur Drajat (Research Synergy Foundation, 2021)
The values of religiosity color the awareness that essentially men and women are equal before God. Because of this, Aisyiyah pioneered the women's movement in all fields, and did not hesitate to cooperate with men. Men and women are given the same potential intellectually, morally and spiritually. Every organization has its own cultural style. This paper is based on the perspective of community practice and stakeholder relations. The research method uses a qualitative method with a case study approach, because it examines the natural environment comprehensively in a single case in the Aisyiyah Women's Organization in Bandung City as one of the pioneer organizations in social movements and women's ruhuddin in Indonesia. Data collection techniques: (1) interviewing the Head of Aisyiyah Regional Leadership (PDA) Bandung City; (2) Focus Group Discussion (FGD) with the management of the Bandung City Economic Council PDA; and (3) distributing questionnaires to representatives of Aisyiyah Branch Managers throughout the city of Bandung. The data analysis was carried out using an interactive model and multiple triangulation for the validity of the data. The results of the study show that the various programs of 'Aisyiyah can continue to run with most of them using information technology tools. Meetings are limited to a few participants, so that organizational meetings attended by thousands of participants can still be held virtually. The group communication facility in WhatsApp groups has become an additional means for organizational consolidation. Meetings as official organizational communication can still be held using the zoom meeting application. Therefore, physical movement restrictions during this pandemic, there are almost no significant obstacles for the Aisyiyah Organization to continue implementing the program.